Traces of Argumentation in the Oratory Fragments of Symmachus - Del Core, Vincenzo (Ciceroniana On Line, 2022)
The orations of Quintus Aurelius Simmachus can only partly be studied within the framework of classical rhetorical analysis. This is for several reasons: first and foremost, because of the fragmentary state of the texts themselves, an element that makes their interpretation difficult, and even more so because of the numerous challenges in reconstructing the texts. Moreover, Simmachus’s speeches exhibit a blending of genres or blurring of generic lines that is common currency in Late Antiquity. In fact, three of the eight speeches are panegyrics (two dedicated to Valentinian I and one to Gratian) and, although at first glance they appear to respect the rules of the genre, at the same time, they reveal peculiarities within them that make them not entirely comparable to other extant encomia in the sylloge of twelve panegyrics attributed to various (not always identifiable) authors between the end of the 3rd and 4th centuries. In light of this, it is not surprising that Simmachus’s eulogies of emperors, although not formally required to persuade an audience, may contain elements typical of judicial and deliberative orations. Persuasion is not an easy task in this context, given that the praise of the princeps must harmonise with the ideological positions that the pagan senatorial aristocracy, deeply tied to a nostalgically republican vision, continued to uphold, despite their progressively diminishing role within the Roman state apparatus. Simmachus employs various argumentative strategies ranging from the usual deployment of sententia and the apposite exemplum, as well as devices like amplification—all of which follows in the tradition of epideictic discourses outlined in Aristotle's Rhetorica. Finally, beyond the purely technical aspect, the paper also aims to show how the structure of Simmachian argumentation is influenced by the political training of the orator, an aspect which draws inspiration from an authentically Ciceronian vision of oratory.